Effect of health education with a leaflet and demonstration on prevention of falls in elderly lymphoma patients during in-hospital chemotherapy for the first time (图文式健康教育在预防老年淋巴瘤患者首次住院化疗期间跌倒的应用效果) - KUANG Meiling (邝梅玲); ZENG Xiujuan (曾秀娟) (中西医结合护理)
Objective To investigate the effect of health education with a leaflet and demonstration on prevention of falls in elderly lymphoma patients during in-hospital chemotherapy for the first time. Methods Totally 60 elderly lymphoma patients with hospital admission between December 2017 and June 2018 were included as the control group, received a routing health education during in-hospital chemotherapy for the first time. Another 60 patients with hospital admission between July 2018 and Jan 2019 were recruited as the observation group, received health education with a leaflet and demonstration. The patients’ awareness of prevention on falls, incidence of falls and patients’ satisfaction of nursing care were compared between two groups. Results The awareness rate of prevention on falls was 91. 67%(55/60) in the observation group, which was higher than 76. 67%(46/60) in the control group (P＜0. 05). There were three cases of falls reported in the control group. Patients in the observation group were more satisfied with nursing care than those in the control group (98. 33 vs. 88. 33%, P＜0. 05). Conclusion The health education with a leaflet and demonstration is effective to improve the patients’ awareness of prevention on falls, therefore reducing the risk of falls during in-hospital chemotherapy for the first time. (目的 探讨图文式健康教育预防老年淋巴瘤患者首次住院化疗期间跌倒的效果。方法 将2017年12月—2018年6月入院的60例患者设为对照组, 2018年7月—2019年1月入院的60例患者设为观察组。对照组予常规口述式健康教育方法对患者进行预防跌倒相关知识宣教, 观察组在对照组基础上开展图文式健康教育。比较2组对预防跌倒知识掌握率、跌倒事件发生率以及对护理工作满意率。结果 观察组对预防跌倒知识掌握良好率91. 67%(55/60), 优于对照组的76. 67%(46/60), 差异有统计学意义(P＜0. 05)。观察组住院期间未发生跌倒, 对照组患者住院化疗期间发生跌倒为3例。观察组患者对护理工作满意度为98. 33%(59/60), 高于对照组的88. 33%(53/60), 差异有统计学意义(P＜0. 05)。结论 图文式健康教育可以提高老年淋巴瘤患者在首次住院化疗期间对预防跌倒安全知识的掌握率以及对护理工作的满意率, 减少跌倒不良事件的发生。)